2014
DOI: 10.3389/fncir.2014.00001
|View full text |Cite
|
Sign up to set email alerts
|

N2A: a computational tool for modeling from neurons to algorithms

Abstract: The exponential increase in available neural data has combined with the exponential growth in computing (“Moore's law”) to create new opportunities to understand neural systems at large scale and high detail. The ability to produce large and sophisticated simulations has introduced unique challenges to neuroscientists. Computational models in neuroscience are increasingly broad efforts, often involving the collaboration of experts in different domains. Furthermore, the size and detail of models have grown to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 32 publications
4
68
0
Order By: Relevance
“…In teleost hindbrain and spinal cord, most gap junctions represent heterologous couplings of axon terminals onto somata and “somatic dendrites” of unlike neurons (Diamond and Huxley, 1968), including sensory neurons coupled to motor neurons (this report) and interneurons coupled to principal or projection neurons (Maler et al, 1981; Serrano-Vélez et al, 2014). This widespread heterologous coupling is in contrast with the often, though not exclusive, homologous coupling found at dendro-dendritic, presumably “purely electrical” synapses in mammalian CNS (Kosaka, 1983; Kosaka and Hama, 1985; Fukuda and Kosaka, 2000a; Kosaka and Kosaka, 2004; Kosaka and Kosaka, 2005; Fukuda et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In teleost hindbrain and spinal cord, most gap junctions represent heterologous couplings of axon terminals onto somata and “somatic dendrites” of unlike neurons (Diamond and Huxley, 1968), including sensory neurons coupled to motor neurons (this report) and interneurons coupled to principal or projection neurons (Maler et al, 1981; Serrano-Vélez et al, 2014). This widespread heterologous coupling is in contrast with the often, though not exclusive, homologous coupling found at dendro-dendritic, presumably “purely electrical” synapses in mammalian CNS (Kosaka, 1983; Kosaka and Hama, 1985; Fukuda and Kosaka, 2000a; Kosaka and Kosaka, 2004; Kosaka and Kosaka, 2005; Fukuda et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Although the thalamus receives strong driver inputs from the peripheral whisker sensors via the brainstem, the majority of the synapses on thalamic neurons originate in cortex (Varela, 2014). In addition, recent evidence has shown that direct corticothalamic feedback onto VPm neurons can lead to a sustained depolarization of the baseline membrane potential (Crandall et al, 2015; McCormick and von Krosigk, 1992; Mease et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As major nodes of the “salience network,” these regions are strongly modulated by DA and NE (Chandler et al, 2014; Cole et al, 2013; Hermans et al, 2011; Seeley et al, 2007) and are amenable to the influence of MPH. Indeed, previous studies have shown that MPH attenuates dACC/insular activity in the context of surprise or error.…”
Section: Discussionmentioning
confidence: 99%